2009
DOI: 10.1097/ta.0b013e31818b2567
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Replacement With Hypertonic or Isotonic Solutions Guided by Mixed Venous Oxygen Saturation in Experimental Hypodynamic Sepsis

Abstract: Although normalization of mixed venous oxygen saturation was not associated with restoration of markers of splanchnic or other systemic perfusion variables, the initial fluid savings with hypertonic saline and its latter effect on gut apoptosis may be of interest in sepsis management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…Quite obviously, the plasma-expander effect of HSL might be related to its hyperosmolarity because a similar effect has been reported with hypertonic saline [17-19]. However, although HSL is hyperosmolar (see Table 1), it is less hypertonic than a sodium-chloride solution with the same osmolarity, because the monocarboxylate carrier allows lactate to cross the cellular plasma membrane [20].…”
Section: Discussionmentioning
confidence: 98%
“…Quite obviously, the plasma-expander effect of HSL might be related to its hyperosmolarity because a similar effect has been reported with hypertonic saline [17-19]. However, although HSL is hyperosmolar (see Table 1), it is less hypertonic than a sodium-chloride solution with the same osmolarity, because the monocarboxylate carrier allows lactate to cross the cellular plasma membrane [20].…”
Section: Discussionmentioning
confidence: 98%
“…Hypertonic fluid administration in a porcine model of acute hyperdynamic endotoxemia resulted in a persistently high oxygen delivery to splanchnic organs (30). In a more recent animal study, hypertonic fluid administration failed to restore splanchnic perfusion variables but reduced the degree of gut epithelial cells apoptosis (31).…”
Section: Discussionmentioning
confidence: 98%
“…The most consistent finding from large animal models of sepsis is that of a short-term improvement in cardiac output associated with fluid resuscitation, with the effect dissipating rapidly after the termination of infusion [7274]. Similarly, a number of studies have demonstrated modest improvements in gastrointestinal perfusion with fluid resuscitation [73]; however, this finding is not consistent in all the animal studies [74].…”
Section: Preclinical Evidence For the Use Of Fluid Resuscitation In Smentioning
confidence: 99%
“…When challenged with intravenous endotoxin, humans also develop a hyperdynamic circulation [34]. This contrasts with the response seen in most large and small animal models, where hypodynamic shock after sepsis or endotoxemia predominates [7274, 76–78, 82, 83]. These disparities occur from both the design characteristics of the models and the differences in human and experimental animal physiology.…”
Section: Preclinical Evidence For the Use Of Fluid Resuscitation In Smentioning
confidence: 99%